VIGILANCIA SEROLÓGICA AL ANTICUERPO CONTRA Yersinia pestis EN PERROS CENTINELA DE POBLACIONES EN RIESGO - García Rodríguez, Jofrey Oliver (2017)
Introduction: Studies show that serological surveillance in dogs is a useful tool in areas with epidemiological silence for plague. Objective: Determine the levels of antibody against Yersinia pestis in sentinel dogs of a population at risk by a latex agglutination test as serological surveillance. Method: An observational prospective analytical in which we worked with 30 dogs over 6 months old who lived in houses and had contact with wild areas and crops, These belonged to the localities of Santa Clara, Mocollope and Santa Elena, they were taken a venous blood sample and the latex agglutination test has been made at the beginning, 3 months and 6 months of follow-up. Results: The titration that came closest to the positivity was 1:64 in Santa Clara. The titration increased 33.33% (X²McN=12, p>0.05) by comparing the first with the third venous blood sample in the total of dogs. The dogs that showed the highest increase in its titration was of Santa Elena, 40% (X²McN=5, p>0.05). When comparing the increase of the titration in the dogs the 3 localities we don´t have significant difference (X²p(2)=0.3030, p>0.05). Conclusions: The levels of antibodies against Yersinia pestis in sentinel dogs varied with a titration between 1:8 and 1:64 according to the localities, without showing positivity when applying the latex agglutination test. Keywords: Sentinel dog, Latex agglutination, Yersinia pestis, population at risk (Source: DeSC BIREME)